Left-symmetric algebra structures on contact Lie algebras. Issue 7 (3rd July 2023) - Méndez-Méndez, F. O.; Salgado, G.
Abstract: The aim of this work is to give necessary and sufficient conditions to extend an LSA structure on a Lie algebra h to a Lie algebra g that either contains h as a subalgebra, or is a central extension of it. We also study conditions under which a Lie algebra together with an LSA structure admit a Frobenius or a contact form. Furthermore, we describe the properties of the Reeb vector associated with the codimension one contact ideal with respect to the LSA structure on the Frobenius Lie algebra.